2014
DOI: 10.1080/09168451.2014.932667
|View full text |Cite
|
Sign up to set email alerts
|

Practical application of flavonoid-poor menu meals to the study of the bioavailability of bilberry anthocyanins in human subjects

Abstract: Practical application of flavonoid-poor menus was evaluated on the bioavailability of anthocyanins as model flavonoids. Detectable amounts of flavonoids were not found in plasma and urine collected from 13 participants, who took the menus. After ingesting bilberry anthocyanins (919 μmol), average plasma AUC0-6h, Cmax, Tmax values and urinary recovery were 386.0 nmol h/mL, 139.1 nM, 1.31 h and 0.21%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Many of the metabolites found in the present study have been shown to have a T max of between 0•5 and 2 h, such as caffeic acid, ferulic acid derivatives and quercetin (42,54) . Similar results were found with the appearance of anthocyanin metabolites after consumption of aronia berries (55) and bilberries (56) , with T max ranging from 1 to 6 h. As processing the blueberries into a juice could also influence bio-accessibility in biological fluids, a single time point gives no information on kinetics of absorption and appearance. Indeed, several studies have shown differences in bioavailability in processed fruit in targeted studies (7,24,50) .…”
Section: Discussionsupporting
confidence: 68%
“…Many of the metabolites found in the present study have been shown to have a T max of between 0•5 and 2 h, such as caffeic acid, ferulic acid derivatives and quercetin (42,54) . Similar results were found with the appearance of anthocyanin metabolites after consumption of aronia berries (55) and bilberries (56) , with T max ranging from 1 to 6 h. As processing the blueberries into a juice could also influence bio-accessibility in biological fluids, a single time point gives no information on kinetics of absorption and appearance. Indeed, several studies have shown differences in bioavailability in processed fruit in targeted studies (7,24,50) .…”
Section: Discussionsupporting
confidence: 68%
“…Pharmacokinetic trial to evaluate the bioavailability of anthocyanins and colonic polyphenol metabolites after consumption of aronia berry extract in plasma and urine [96] Pharmacokinetic characterization and bioavailability of strawberry anthocyanins relative to meal intake [97] Bioavailability studies and anticancer properties of malvidin-based anthocyanins, pyranoanthocyanins and nonoxonium derivatives [98] Effect of red cabbage fermentation on anthocyanin bioavailability and plasma antioxidant capacity in humans [99] Bioavailability of red raspberry anthocyanins and ellagitannins: new insights [82] Bioavailability and uptake of anthocyanins and their metabolites from grape/blueberry juice and smoothie in vivo and in vitro [100] Tissue bioavailability and intake of tart cherry anthocyanins [101] Confirmation and identification of tart cherry anthocyanins in several target tissues of healthy rats [102] Bioactive anthocyanins in 'Queen Garnet' plum: maturity and bioavailability [103] Use of anthocyanins as bioactive colourants in lipstick formulations [104] Application of the developed flavonoid-poor menu meals to the study of the bioavailability of bilberry anthocyanins as model flavonoids [105] Anthocyanin stability, mucus binding, and uptake into epithelial cells in healthy individuals that retained red grape or chokeberry juice in the mouth [106] Absorption and bioavailability of anthocyanins across the gastrointestinal mucosa [107] Effects of processing sour cherry fresh fruit to the final juice product on the content of anthocyanins and other related polyphenols [108] …”
Section: Comments Referencesmentioning
confidence: 99%
“…Anthocyanins are hydrophilic compounds, predictably unable to cross the cell plasma membrane by passive diffusion (9). Therefore, without a hydrophilic carrier, such as the NNS, which also have a hydrophobic, fatty acid component that ʻmeltsʼ into cell membranes to deposit the Bilberry into the cancer cells, one could understand the poor bioavailability of the anthocyanins (10,11). The results obtained show that the bilberry extract does have an increased anti-cancer effect when it is encapsulated compared to the free compound.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of this NNS preparation enables its combination with other NNS supplements by simply adding drops together in a beverage. Some of the NNS preparations that have been successfully micellized using the NNS methodology include Vitamins (C, B12, D 3 , E), CQ 10 , Curcumin, Artemisinin, Frankincense, Riboside Nucleotide, Acemanan, among others. Finally, all of our NNS preparations survive the stomach and intestines and fuse with the intestinal cell walls and deposited into the bloodstream with a bioavailability exceeding 90%.…”
Section: Discussionmentioning
confidence: 99%